THE USE OF BATAVIA LANGUAGE IN EAST JAKARTA (STUDY OF SOCIODIALECTOLOGY) - Nur Irwansyah (Universitas Indraprasta PGRI, 2020)
Abstract: This research is to describe the use of Betawi language used by native speakers or natives or at least have lived for ten years in East Jakarta with sociodialectological studies which include descriptions of the use of Betawi in phonology and lexical fields as well as descriptions of similarities and differences in Betawi in East Jakarta. The research method used is a comparative descriptive method. Data collection is done using the method of field mixing, which is a method of collecting data directly or verbally. In addition, the method used is the synergy method. Research techniques used, namely note taking and fishing techniques. The conclusion of this research is the existence of several similarities and differences, both in the fields of phonology, morphology, lexicon, or syntax. From the 806 words we obtained from speakers in each region, researchers found 235 differences in the same lexicon and 571 lexicon in the four study areas. The conclusion of this research is at the level of phonology, morphology, lexicon, and syntax there is considered no difference. Keywords: Language, Betawi, East Jakarta.